2016
DOI: 10.7763/ijcea.2016.v7.552
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and Identification of Antioxidant Compounds from Bran of Thai Black Rice cv. Riceberry

Abstract: Abstract-Bran of Thai Black Rice cv. Riceberry was extracted using solvent extraction (hexane, dichloromethane and methanol). The crude extracts obtained were investigated for their antioxidant property and total phenolic contents which were assessed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay and Folin-Ciocalteu's method, respectively. Results showed that the methanolic extract had the strongest total antioxidant activity and phenolic content at 97.83 % and 9.87 mg GAE/ml of extract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Based on the Folin-Ciocalteu assay, RB extract in this study contained phenolic compounds approximately 13 mg GAE/g. It has been reported that the top three phenolic compounds found in Thai RB extract included 2-methoxy-vinyl phenol, catechol, and guaiacol [32]. Besides, the documented anthocyanidins in RB extract were cyanidin-3-glucoside and peonidin-3-O-glucoside [68].…”
Section: Effect Of the Volume Ratio Of Agno 3 To Rb Solution Onmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the Folin-Ciocalteu assay, RB extract in this study contained phenolic compounds approximately 13 mg GAE/g. It has been reported that the top three phenolic compounds found in Thai RB extract included 2-methoxy-vinyl phenol, catechol, and guaiacol [32]. Besides, the documented anthocyanidins in RB extract were cyanidin-3-glucoside and peonidin-3-O-glucoside [68].…”
Section: Effect Of the Volume Ratio Of Agno 3 To Rb Solution Onmentioning
confidence: 97%
“…The purple rice barn extracts have been reported to have antioxidants, anti-inflammatory, anticancer [30], and antidiabetic activities [31]. The major constituents in a crude extract of RB bran are phenolic compounds [32], which possess hydroxyl (-OH) and carboxyl (-COOH) groups. These functional groups are capable of reducing the Ag + in an aqueous solution to form metallic silver.…”
Section: Introductionmentioning
confidence: 99%
“…2,2'-((1E,1'E)-(1,4phenylenebis(azanylylidene))bis(methanylylidene))diphenol (Nitrilo methyl dyne) has been reported to have an anti-tumor activity (Kopoytkoba & Caxho, 2019).The compound 7hydroxy-3-methoxy-2-(4-methoxyphenyl)-4H-1-benzopyran-4-one that is identified to possess antioxidant activity from the bran of Thai black rice (Suttiarporn et al, 2016) and 5,7-dihydroxy-2-(4-hydroxyphenyl)-6-methoxy-4H-chromen-4-one reported to have strong antioxidant activity (Karker et al, 2019;Mu et al, 2009;Yausheva et al, 2019). 2,3,7,8tetramethoxy-5,11-dihydro10H-dibenzo[a,d][7]annulen-10-one has anti-inflammatory activity (Fernandes & Krishnan, 2019).…”
Section: Gc-ms Analysis Of Leaf Methanolic Extractmentioning
confidence: 99%
“…Many pigmented rice cultivars have been reported to contain high levels of nutrients with high potential to promote human health due to the great antioxidant potency of their phytochemicals such as phenolics, anthocyanidins, flavonoids, folate, vitamin E, and β-carotene [1]. Thai riceberry rice has been developed to provide nutritional benefits to consumers and to be a medical supplement for type 2 diabetes and anaemia patients because it contains a high amount of iron and has a low glycaemic index [2].…”
Section: Introductionmentioning
confidence: 99%